A Two-Dimensional Partitioning of Fracture–Matrix Flow in Fractured Reservoir Rock Using a Dual-Porosity Percolation Model - Jinhui Liu; Yuli Zhou; Jianguo Chen (Energies, 2021)
Fractures and micropores have varying contributions to the gas permeability of fractured reservoirs. The quantification of the contribution of fractures and micropores that form a dual-porosity system for gas permeability is critical when attempting to accurately evaluate gas production. However, due to insufficient knowledge of fracture–matrix flow partitioning in such dual-porosity systems, it is challenging for previous models to quantitatively characterize the fracture heterogeneity and accurately evaluate the gas flow and permeability in fractured rocks. In this study, we propose a dual-porosity percolation model to quantitatively investigate the contributions of fractures and matrix micropores towards the gas permeability of fractured rocks. Using percolation theory, we establish fracture networks with complex heterogeneity, which are characterized by various fracture densities and percolation probabilities within a porous matrix with various fracture/matrix permeability ratios. The compressible Navier–Stokes and Brinkman equations were adopted to describe the gas flow in the fractures and porous matrix, respectively. The simulation results indicate that the gas permeability of the dual-porosity system has an exponential relationship with the fracture density and matrix permeability. The contribution of fractures and matrix micropores toward gas permeability can be classified by establishing a two-dimensional partitioning of the fracture–matrix flow related to the fracture heterogeneity and fracture/matrix permeability ratio. The contribution of matrix micropores cannot be neglected if the fracture density is lower than a critical value.